Guillain-Barré Syndrome in Patient With SARS-CoV-2 PCR Positivity Treated Successfully With Therapeutic Exchange Plasma: A First Case Report From Vietnam - Duong-Quy, Sy; Huynh-Truong-Anh, Duc; Nguyen-Thi-Kim, Thanh; Nguyen-Quang, Tien; Nguyen-Chi, Thanh; Tran-Xuan, Quynh; Nguyen-Nhu, Vinh; Ngo, Carine; Craig, Timothy (Frontiers in Neurology, 2022)
Since the first case of Guillain-Barré syndrome (GBS)-associated SARS-CoV-2 (COVID-19) infection reported in 2020, a series of cases have been published in some countries. In this case report, we present a young patient with GBS, whose clinical and laboratory data were appropriate for the diagnosis of GBS due to COVID-19 infection. Neurological examination revealed the muscular weakness of lower limbs with Medical Research Council (MRC) scale of 2/5 associated with diminished reflexes. Laboratory studies showed the positive nasal swab RT-PCR test for COVID-19, leukopenia, increased ferritin and LDH levels, normal electrolyte and liver and kidney function, and normal chest X-ray. The result of cerebrospinal fluid showed the albuminocytologic dissociation. The patient was treated with remdesivir, dexamethasone, anticoagulation, and therapeutic plasma exchange (TPE). Patient's muscle weakness was significantly improved after 1 week of admission. He was discharged at 23rd days of hospitalization and followed-up in the out-patients department.